On the theory of the boundary behavior of mappings of the Sovolev class on Riemann surfaces - Volkov, S.V.; Ryazanov, V.Y. (Reports of the National Academy of Sciences of Ukraine, 2016)
In terms of dilatations, a number of criteria for a homeomorphic extension to the boundary of mappings in the Sobolev class between domains on Riemann surfaces are formulated.